Variation Orders Causes in Construction Buildings Projects in Jordan - Albtoosh, Ja’far A. Aldibat; Ahmad Tarmizi, Haron (GJESRM, 2017)
Generally, by review causes and issues related to V.O in construction projects, the aim of this paper is to investigate the real cause of variation orders in its root stage, This paper investigates the most significant causes contribute to the variation orders in the construction of building projects in Jordan, data was collected from questionnaire survey which is based on the literature reviews. The data were analyzed by using mean score method and rank to formulate the findings. The results from questionnaire survey revealed three most significant causes variation orders which are: Errors and omission in design delay in completion and increase project cost Change in specification by owners The finding concluded that employer us the main originator of the variation orders and suggested that owner should have adequate planning and recourses before initiating a project in order to avoid variation order during the construction stage.